Inhibiting SIRT-2 by AK-7 restrains airway inflammation and oxidative damage promoting lung resurgence through NF-kB and MAP kinase signaling pathway - Yadav, Vandana; Pandey, Vinita; Gaglani, Pratikkumar; Srivastava, Atul; Soni,; Subhashini, (Frontiers in Immunology, 2024)
Chronic obstructive pulmonary disease (COPD) is a major global cause of mortality with limited effective treatments. Sirtuins (SIRT) are histone deacetylases that are involved in regulation of redox and inflammatory homeostasis. Hence, the present study aims to investigate the role of SIRT-2 in modulating inflammation in murine model of COPD. COPD in mice was established by cigarette smoke (CS) exposure for 60 days and AK-7 was used as specific SIRT-2 inhibitor. AK-7 (100µg/kg and 200µg/kg body weight) was administered intranasally one hour before CS exposure. Molecular docking was performed to analyse the binding affinity of different inflammatory proteins with AK-7. Immune cells analysis showed significant increased number of macrophages (F4/80), neutrophils (Gr-1) and lymphocytes (CD4 + , CD8 + , CD19 + ) in the COPD group and their population was declined by AK-7 administration. Total reactive oxygen species, total inducible nitric oxide synthase, inflammatory mediators such as neutrophil elastase, C-reactive protein, histamine and cytokines as IL4, IL-6, IL-17 and TNFα were elevated in COPD and declined in AK-7 groups. However, IL-10 showed reverse results representing anti-inflammatory potency. AK-7 administration by inhibiting SIRT-2 decreased the expression of NF-κB, p-P38, p-Erk, p-JNK and increased Nrf-2 expression. Further, AK-7 also declined the lung injury by inhibiting inflammation, parenchymal destruction, emphysema, collagen, club cells and kohn pores. AK-7 also showed good binding affinity with inflammatory proteins. The current study reveals that SIRT-2 inhibition mitigates COPD severity and enhances pulmonary therapeutic interventions, suggesting AK-7 as a potential therapeutic molecule for COPD medication development.